Prevalence of oncogenic human papillomavirus in pregnant adolescents, association with colpocytological changes, risk factors and obstetric outcomes (Clinics, 2022)
Purpose: The authors aim to carry out an investigation on the impact of cervical oncogenic Human Papillomavirus (HPV) detection in pregnant adolescents, to clarify the prevalence and risk factors, considering the importance and lack of data on this topic in Brazil.Methods: A cross-sectional study was conducted with adolescents receiving prenatal care in a tertiary hospital in São Paulo, Brazil, with routine Pap smear and oncogenic HPV detection test in the uterine cervix. The authors sought to associate the results of these tests with demographic and obstetric variables.Results: A total of 303 pregnant adolescents whose mean age was 15.30 ± 1.22 years comprised the study subjects. The frequency of high-risk HPV cervical detection was 50.50%. Multivariate analysis revealed that a large number of partners in their lifetime (OR = 1.27) and having a religion (OR = 2.05) were risk factors for cervical detection of oncogenic HPV, while schooling appeared as a protective factor (OR = 0.85). There was an association between this detection and colpocytological alterations, reaching almost 30% of patients, but without association with obstetric and neonatal outcomes.Conclusion: The prevalence found is one of the highest in Brazil and worldwide. A greater number of partners during their lifetime and having religion were detected as possible factors associated with cervical HPV detection. Detection of cervical HPV-DNA did not influence obstetric and neonatal outcomes. The findings of this study reinforce the need to implement educational measures capable of modifying the incidence of sexually transmitted infections in this population and capable of promoting adherence to HPV vaccination programs.